‘Big’ and ‘little’ Quo Vadis? in the United States, 1913–1916: Using GIS to map rival modes of feature cinema during the transitional era - Klenotic, Jeffrey (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
This article emanates from a geospatial database of over 600 premieres of the Cines company’s Quo Vadis? (1913), an eight-reel film distributed by George Kleine, and nearly 250 premieres of the Quo Vadis Film Company’s Quo Vadis? (1913), a three-reel film of ambiguous origins distributed by Paul De Outo. By mapping local premieres of both films across the United States from 1913 through 1916, the data show with spatiotemporal precision the spread of Quo Vadis? as one of cinema’s early blockbuster titles. Yet within this national phenomenon, the two films’ footprints reveal differing cultural geographies served by competing efforts to feature Quo Vadis? using alternative practices of distribution and exhibition. The study finds that Quo Vadis? played a more complex role mediating the rise of features than is yet known, serving rival modes of cinema where longer, more expensive films were celebrated but also contested.